Ecological deontology at the interior of the Postmodern - Matviychuk, Andriy (Skhid, 2013)
Filed grounding philosophical and methodological relevance of new scientific field - ecological deontology. The author uses as a methodological lens ideas and principles of postmodern philosophy.